2017
DOI: 10.1007/s00223-017-0329-5
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perceptions are Associated with Quality of Life in Patients with Fibrous Dysplasia

Abstract: Fibrous dysplasia (FD) is a rare bone disorder in which normal bone is replaced by fibrous tissue resulting in pain, deformities, pathological fractures or asymptomatic disease. Illness perceptions are patients’ cognitions and emotions about their illness and its treatment, which may impact on Quality of Life (QoL). Here, we explore illness perceptions in patients with FD compared to other disorders, identify factors associated with illness perceptions and evaluate their relationship with QoL. Ninety-seven out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Among the three factors in the hypothetical model extracted by CFA, somatic focus was the most frequently associated with HRQOL, low back pain, and dysesthesia in our cohort although there are reports that older adults with chronic pain had lower kinesiophobia. 51 As it has been reported that illness perception was related to HRQOL in patients with fibrous dysplasia, 52 subjective health is determined by referring to the perception of one’s own health status: the stronger the perception of poor health, the stronger the pain and abnormal sensation, and the lower the HRQOL. On the other hand, activity avoidance and efficacy of physical activities were considered to be indirectly related to HRQOL, although they were weakly related to HRQOL and pain or dysesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three factors in the hypothetical model extracted by CFA, somatic focus was the most frequently associated with HRQOL, low back pain, and dysesthesia in our cohort although there are reports that older adults with chronic pain had lower kinesiophobia. 51 As it has been reported that illness perception was related to HRQOL in patients with fibrous dysplasia, 52 subjective health is determined by referring to the perception of one’s own health status: the stronger the perception of poor health, the stronger the pain and abnormal sensation, and the lower the HRQOL. On the other hand, activity avoidance and efficacy of physical activities were considered to be indirectly related to HRQOL, although they were weakly related to HRQOL and pain or dysesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…10, No. 7;2018 their illness by themselves and understand their illness and symptoms well. Furthermore, the patients felt that T2DM does not have serious consequences, so they do not worry and do not think too much about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the protocol used in our ongoing study addressing various aspects of QoL in patients with FD [ 1 , 4 ], three different questionnaires were sent to 255 consecutive patients with a confirmed diagnosis of FD, aged ≥ 16 years, who attended the outpatient clinic of the Centre for Bone Quality of the Leiden University Medical Center between 2013 and 2016. Ninety-two of 138 eligible patients completed the questionnaires, representing a response rate of 67% (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The second stage consists of coping strategies that are developed based on illness perceptions. In a previous study of our department, it was demonstrated that illness perceptions of patients with FD differed significantly from patients with acute or chronic pain due to other medical conditions [ 4 ]. The third stage of the CSM consists of the effect of these coping strategies on the patient’s QoL.…”
Section: Introductionmentioning
confidence: 99%